2014
DOI: 10.1111/ejh.12419
|View full text |Cite
|
Sign up to set email alerts
|

Determination of deferasirox plasma concentrations: do gender, physical and genetic differences affect chelation efficacy?

Abstract: The results could indicate that a higher plasma DFX concentration could be associated with greater chelation efficacy. As a correlation between dose and CDFX was not demonstrated, it seems useful to monitor the concentrations to optimize and determine the most appropriate dose for each patient. Interesting results emerged from the analysis of genetic and physical characteristics of patients: LBM was a borderline significant effect modifier of the relationship between UGT1A1 polymorphisms and CDFX . Individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Measurement, by high performance liquid chromatography (HPLC) assay, previously described and validated, 12 , 13 of DFX plasma concentration confirmed a moderate increase of the drug plasmatic level (C trough =27 µM; normal C trough value <20 µM; C DFX /D DFX ratio =0.56). Tacrolimus therapeutic plasma concentrations were maintained at about 10 ng/mL.…”
Section: Case Reportsmentioning
confidence: 71%
“…Measurement, by high performance liquid chromatography (HPLC) assay, previously described and validated, 12 , 13 of DFX plasma concentration confirmed a moderate increase of the drug plasmatic level (C trough =27 µM; normal C trough value <20 µM; C DFX /D DFX ratio =0.56). Tacrolimus therapeutic plasma concentrations were maintained at about 10 ng/mL.…”
Section: Case Reportsmentioning
confidence: 71%
“…DFX glucuronidation is controlled by the UDP-glucuronosyltransferase 1A subfamily (UGT1A1 and, to a lesser extent, UGT1A3). UGT1A1 polymorphism has been recognized as an important element in drug tolerance because it increases the risk of toxicity of drugs metabolized via glucuronidation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deferasirox plasma concentrations (C-DFX) were determined by high performance liquid chromatography (HPLC) assay, as previously described and validated [ 10 , 11 ]. Plasma samples were processed by liquid–liquid extraction using methanol.…”
Section: Methodsmentioning
confidence: 99%
“…observed that twice‐daily DFX administration increased C trough compared with once‐daily route, suggesting that drug levels are dose related. Concerning drug efficacy, Mattioli et al . indicate that a higher plasma DFX concentration could be associated with greater chelation efficacy, suggesting the usefulness to monitor drug concentrations to determine the appropriate dose for each patient.…”
Section: Discussionmentioning
confidence: 99%